Correlation between oxygen reserve index monitoring and blood gas oxygen values during anesthesia in robotic total prostatectomy surgery - Hilal Zengin (BMC Anesthesiology)
Abstract Introduction-objective Hyperoxia is associated with acute lung injury and atelectasis. Arterial blood gas measurement is an invasive method. The Oxygen Reserve Index (ORI) was developed to monitor the oxygen values of patients. In this study, we aimed to find out whether safe monitoring against hyperoxia could be achieved in Robotic-Assisted Radical Prostatectomy (RARP) operations by using ORI, which is an easier measurement method compared to arterial blood gas measurements. Materials and methods The study was carried out with adult male patients over the age of 18 who underwent RARP with the diagnosis of prostate cancer. An ORI pulse oximeter was additionally attached to their index fingers for ORI monitoring. The moment when ORI values were first read was considered the baseline, and arterial blood gas and ORI values were recorded simultaneously at the baseline (T1), 30 min later (T2), 1 h later (T3), 3 h later (T4), and 5 h later (T5). The correlations between the simultaneously recorded ORI and arterial blood gas values were analyzed. Results The sample of the study included 24 male patients. The mean age of the patients was 63.30 ± 7.74, their mean BMI (kg/m2) was 26.64 ± 2.84, and their mean duration of operation was 351.52 ± 48.72 min. The mean ORI value in all measurements was 0.36 (median: 0.28, SD: 0.3694). In the ROC curve analysis conducted to determine the optimal cut-off point for ORI to detect PaO2 ≥ 150 mmHg, the AUC was 0.901 (95% CI: 0.821–0.981), and the cut-off value obtained based on the ROC curve (cut point ORI) was 0.220 (sensitivity: 0.826, specificity: 0.771). The results of the linear regression analysis showed a strong relationship between ORI and PaO2 (PaO2 < 240 mmHg) [simple linear regression, n = 90; r 2  = 0.505, p < 0.001]. Conclusion The results of this study demonstrated a significant connection between ORI and PO2 values in their simultaneous interpretation at PO2 values lower than 240. Because the sensitivity of ORI to PO2 is low in cases of severe hyperoxia, blood gas analyses will be needed.